2019
DOI: 10.5222/tmcd.2019.061
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candida parapsilosis Complex Strains Isolated from Blood Samples at Species Level and Determination of Their Antifungal Susceptibilities

Abstract: ÖZ Amaç: Dünyada ve ülkemizde birçok merkezde, fırsatçı bir enfeksiyon olan kandidemilere ikinci sıklıkta neden olan tür Candida parapsilosis tür kompleksidir. Bu tür kompleksi içinde yer alan Candida parapsilosis sensu stricto, Candida orthopsilosis ve Candida metapsilosis türleri fenotipik olarak birbirinden ayrılamaz ve tanımlanmaları için çeşitli moleküler yöntemlere gereksinim duyulur. Bu çalışmada, laboratuvarımızda kan kültürlerinden izole edilen C. parapsilosis tür kompleksi suşlarının antifungal duyar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The studies from Turkey revealing species‐level distribution of C. parapsilosis complex isolates are scarce, yet similar results were reported. Studies from different time periods identified most of the C. parapsilosis complex isolates as C. parapsilosis sensu stricto 11,16,19,38 . In this study, all of the 181 candidemia episodes investigated through 21 years was caused by C. parapsilosis sensu stricto (99.4%), except one episode caused by C. orthopsilosis (0.4%).…”
Section: Discussionmentioning
confidence: 60%
“…The studies from Turkey revealing species‐level distribution of C. parapsilosis complex isolates are scarce, yet similar results were reported. Studies from different time periods identified most of the C. parapsilosis complex isolates as C. parapsilosis sensu stricto 11,16,19,38 . In this study, all of the 181 candidemia episodes investigated through 21 years was caused by C. parapsilosis sensu stricto (99.4%), except one episode caused by C. orthopsilosis (0.4%).…”
Section: Discussionmentioning
confidence: 60%
“…Similar to fluconazole, voriconazole resistance was also found to be high in C. parapsilosis strains. In addition, the fluconazoleresistant C. glabrata strain was found to be resistant to voriconazole as well, and it is considered to be due to cross-resistance between azole drugs [17,21].…”
Section: Discussionmentioning
confidence: 99%